2018
DOI: 10.1186/s12859-018-2331-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of drug resistance in HIV protease

Abstract: BackgroundDrug resistance in HIV is the major problem limiting effective antiviral therapy. Computational techniques for predicting drug resistance profiles from genomic data can accelerate the appropriate choice of therapy. These techniques can also be used to select protease mutants for experimental studies of resistance and thereby assist in the development of next-generation therapies.ResultsThe machine learning produced highly accurate and robust classification of HIV protease resistance. Genotype data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Vectors were generated for each sequence by obtaining the neighbors of each position of this sequence from the Delaunay triangulation as was done in [ 7 – 9 , 11 , 15 , 17 ]. The coordinates of the carbon atoms were used, and all arcs of the triangulation were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vectors were generated for each sequence by obtaining the neighbors of each position of this sequence from the Delaunay triangulation as was done in [ 7 – 9 , 11 , 15 , 17 ]. The coordinates of the carbon atoms were used, and all arcs of the triangulation were used.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work [ 7 – 9 , 11 , 15 , 17 ] has concentrated on developing models for predicting the resistance to single inhibitors. Shen et al [ 11 ] and Pawar et al [ 17 ] demonstrated classification accuracies higher than 99%. However, many of the resistant strains have lost susceptibility to all clinical inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, these drug-resistant haplotypes will begin to dominate over time [102,113]. The second problem is that drug resistance is connected with haplotypes rather than with the mutations themselves, but haplotypes are harder to detect and so the drug resistance analysis can be significantly improved with more sensitive haplotyping tools [114].…”
Section: Predicting Drug Resistancementioning
confidence: 99%
“…The hypothetical examination of cooperations relies upon heterogeneous wellsprings of organic data, for example, succession and basic information bases, the writing, and exploratory information. The principle data sets containing trial data about proteinprotein collaborations are: the Database of Interacting Proteins (DIP) [17], the Biomolecular Interaction Network Database (BIND) [18], the Molecular Interaction Database (MINT) [19], INTACT [20,21], and Human Protein Reference Database (HPRD) [22]. The writing information on chose protein successions is accessible from the iHOP [23] and STRING [24] data sets.…”
Section: Introductionmentioning
confidence: 99%